Students' Perceptions of Clinical Education during a Global Pandemic - Pologruto, Pamela; Jewell, Jennifer; Cruz, Laura (Journal of Health and Allied Sciences NU, 2021)
Introduction Clinical education is an essential component of allied health programs. The coronavirus disease 2019 (COVID-19) global pandemic had significant impacts on clinical education. The central purpose of this research was to recognize student perceptions of the impact of COVID-19 on their face-to-face clinical experiences during the global pandemic.Methods A Qualtrics survey was sent to 80 physical therapist assistant students whose clinical education was affected during the 2019 to 2020 academic year. Subjects were asked about the following: factors that influenced their decision to complete clinical rotations during the pandemic; perceptions of learning, safety, and stress under these conditions as well as perceptions of the effectiveness of clinical preparatory activities.Results Twenty-six responses to the survey were received and analyzed using descriptive statistics and nonpaired t-tests calculated for each scaled survey item to compare groups. A majority (83.3%) of the respondents reported graduation followed by professional experience (58.3%) as extremely important factors of consideration for participation in clinical education. Personal safety (33.3%) ranked the lowest of the extremely important factors. In preparing for the clinical experience, 75% reported that individual or small group meetings with the faculty member were extremely helpful. The majority of students (78.26%) strongly agreed that they learned a great deal from the clinical experiences under global pandemic; however, 52.17% reported they found the clinical experiences to be stressful.Conclusion During the global pandemic, students placed greater value on interpersonal, trusted relationships when seeking information. Even though students felt stressed during their clinical education, they perceived that learning did occur. As the impacts of COVID-19 remain, physical therapy programs can use this data to recognize areas that require increased support and preparation for students' clinical experiences to encourage an impactful and sustainable future in clinical education.
Keywords: clinical education; COVID-19; health-care literacy; physical therapist assistant